Fulminant myocarditis treated with high doses of steroids - Rycaj, Jarosław; Obersztyn, Anna; Morzyk, Anita; Białkowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
We present the case of a 4.5-year-old girl suffering from a fulminant type of myocarditis who was admitted to our clinic in a very poor condition due to cardiogenic shock. After treating her by invasive methods and very aggressive pharmacotherapy (catecholamines, high doses of steroids, human immunoglobulin), she fully recovered.